What are appropriate treatment goals for hypertension in patients over age 80?. Issue 6 (June 2016) - Castelli, Gregory; Bruehlman, Richard
Abstract : Evidence‐Based Answer : In patients 80 years of age or older, the treatment goal for hypertension is a blood pressure of less than 150/90 mmHg, as there is no clear advantage to targeting a lower goal (SOR: A, consistent findings of high‐quality RCTs).